Predicting Progressive Hemorrhagic Injury Following Traumatic Brain Injury by the Evaluation of D-Dimer/Fibrinogen Ratio - Patidar, Akshay; Chaudhary, Anurag; Sharma, Vinod; Gupta, Ashok (Indian Journal of Neurotrauma, 2024)
Prognosis of traumatic brain injury (TBI) significantly depends on the incidence of progressive hemorrhagic injury (PHI). The present study was conducted to assess whether D-dimer/fibrinogen ratio can predict PHI among the patients with TBI.A total of 150 patients were included in this retrospective study; among them 72 had PHI and 78 did not have PHI. Demographic, clinical, radiological, and laboratory parameters including plasma D-dimer and plasma fibrinogen levels and subsequently D-dimer/fibrinogen ratio were evaluated. Independent t-test, Mann–Whitney U test, chi-square test, Fisher's exact test, and multivariate logistic regression were used for statistical analysis.Age, injury time, first computed tomography time, Glasgow Coma Scale scores, unreactive pupils, abnormal cisterns, midline shift above 5 mm, skull base fracture, epidural hematoma, subdural hematoma, intraventricular hemorrhage, cerebral hematoma, brain contusion, plasma D-dimer concentration, plasma fibrinogen concentration, and D-dimer/fibrinogen ratio vary significantly between PHI and non-PHI groups (p < 0.05). Multivariate logistic regression showed that the Glasgow Coma Scale score (odds ratio [OR], 0.531; 95% confidence interval [CI], 0.436–0.648; p = 0.004) and D-dimer/fibrinogen ratio (OR, 3.784; 95% CI, 2.086–6.867; p = 0.027) were the two independent predictors for PHI.D-dimer/fibrinogen ratio is a useful parameter in predicting the incidence of PHI among the patients with TBI.
Keywords: D-dimer/fibrinogen ratio; Glasgow Coma Scale; plasma fibrinogen; traumatic brain injury; progressive hemorrhagic injury